Optical Correction of Keratoconus with a Scleral Gas-Permeable Lenses - A. V. Myagkov; Yu. B. Slonimskiy; E. V. Belousova; T. S. Mitichkina; L. R. Bunyatova (Oftalʹmologiâ, 2019)
The optical properties of the cornea are determined by its ability to refract and transmit light. Keratoconus changes cornea’s shape, the surface of the cornea becomes irregular, which leads to a violation of light refraction and the occurrence of optical aberrations. The progressing course of the disease and its late detection lead to a delayed start of therapeutic measures, which affects the prognosis of the disease progression and reduces the patient’s quality of life. The quality of visual functions depends on the stage of the process. There are 4 stages of keratoconus (according to M. Asler), each of which corresponds to certain changes in refraction and degree of deformation of the cornea. Early biomicroscopic signs are: “dilution” of the stroma (inhomogeneity of the cornea and a grayish tint in the zone of the developing apex), change in the shape of endothelial cells and clearly visible nerve endings due to longitudinal thickening. In the second stage of keratoconus, the biomicroscopic picture is complemented by the appearance of keratoconus lines (Vogt’s striae). The opacities of the Bowman’s membrane indicate the beginning of the scarring process and the transition of the disease to its third stage. The fourth stage of the disease is characterized by further development of stromal opacities and the occurrence of gross changes of the Descemet’s membrane. Advanced medical equipment for topographic mapping and measuring the cornea makes it much easier for ophthalmologists to diagnose keratoconus and choose more effective treatment methods: crosslinking or surgical treatment. Later it allows to stabilize keratoconus, but does not provide high visual acuity due to the induction of optical aberrations, including high order optical aberrations. Contact lens vision correction is the main way to correct the refractive error resulting from keratoconus. However, the use of corneal gas permeable or soft contact lenses cannot provide high quality vision, additionally causing discomfort associated with their excessive mobility. The use of scleral gas permeable contact lenses is the most effective method of optical correction of all stages of keratoconus and after keratoplasty.